Book Review Essay: “What Was Analysis?" A Review of Mohamed Tal’s "The End of Analysis: The Dialectics of Symbolic and Real" - Edward Dioguardi (EJP import test, 2024)
Review of The End of Analysis: The Dialectics of Symbolic and Real by Mohamed Tal, Palgrave Macmillan, 2023, pp. 143
Keywords: Lacan; Freud; jouissance; Symptom; Christ